Mapping innovations : patents and the sustainable development goals. (WIPO publication ;, 2024)
"This report maps global patents to the United Nations Sustainable Development Goals (SDGs), providing invaluable insights into patent trends aligned with the SDGs. It illustrates patenting activities relevant to the SDGs and the state of technology development across these goals. Utilizing the WIPO Technology Concordance, the report analyzes the alignment between specific technology fields and the SDGs. The study further investigates the geographical locations of inventors and jurisdictions for protecting SDG-related patents. Additionally, a detailed analysis of patent owners headquartered in five key regions is presented, highlighting their pivotal role in driving sustainable innovation across various industries."--